Perancangan Produk Standing Frame (Alat Terapi Berdiri) Bagi Penyandang Disabilitas Cerebral Palsy - Septiana Sinurat, Artha; Ayu Siagian, Ester; Sitanggang, Franciscus; Agustina Panjaitan, Kathrin Rut; Manalu, Lyandry; Uly Tampubolon, Nathasya Dona; Manalu, Windy; Simamora, Yenny Adriyanti; Siboro, Benedikta Anna Haulian (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 8 No 2 (2022): Volume 8 No 2 Tahun 2022, 2023)
Treatment for cerebral palsy is mostly done through physical therapy, behavioural therapy, speech therapy, nutrition, drugs and surgical intervention, but not many uses therapeutic aids. This study aims to design therapeutic aids for children with cerebral palsy disabilities so that they can stand properly using the House of Quality (HOQ) and ergonomics methods. Attributes and specifications for designing therapeutic tools are carried out by observing, asking questions and distributing questionnaires to the companions of children with cerebral palsy. The results of the questionnaire processing provided very important attributes of therapeutic aids as customer requirements (CR), namely the sturdy retaining pole, comfortable to use, anti-slip, economical price and safe to use. The technical requirements (TR) that are prioritized in the development of this product are products that can be disassembled, foot and hand belts made of cloth, strong locking retratos, sturdy wheels and locks. The dimensions of this therapy tool use Indonesian anthropometric measurements for children aged 6-12 years. Dimensions and TR are poured into the design. The design results are then made into a standing frame therapy device which is also equipped with a table to place food and games. The standing frame has been tested and is expected to be used as a therapeutic aid for children with cerebral palsy.